Eksistensi Kewenangan Pemerintahan Dalam Mengatasi Status Kewarganegaraan Bagi Anak Dari Perkawinan Beda Negara - Rifandhana, Raditya Feda (Universitas Brawijaya, 2023)
This research examines the existence of government authority in overcoming the status of citizenship for children from marriages between different countries, as well as reviewing the existence of Law Number 12 of 2006 concerning Citizenship. This normative juridical research has the purpose of analyzing the problems using legal theory, so that the existence of a statutory approach and legal theory can have a positive impact, resulting in the existence of government in addressing the status of children born from interstate marriages, and producing an existence in citizenship laws can meet the needs of citizens.